2022
DOI: 10.1186/s12954-022-00715-4
|View full text |Cite|
|
Sign up to set email alerts
|

Substance use, injection risk behaviors, and fentanyl-related overdose risk among a sample of PWID post-Hurricane Maria

Abstract: Background While natural disasters like hurricanes are increasingly common, their long-term effects on people who inject drugs are not well understood. Although brief in duration, natural disasters can radically transform risk environments, increasing substance use and drug-related harms. Methods Based on a study of people who inject drugs (PWID) and injection risk behaviors in rural Puerto Rico, the present study uses data from two different phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…While we found that there were various patterns (no change, increase, and decrease in substance use patterns), other studies have mostly found that substance use increased after a natural disaster. For instance, a study of substance use after Hurricane Maria found that, among people who inject drugs, increased from 3 to 23% after the storm (Abadie et al, 2022). After Hurricane Katrina, a study found that smoking cigarettes, drinking alcohol, and having alcohol consumption related problems were reported at a much higher rate than before the hurricane.…”
Section: Discussionmentioning
confidence: 99%
“…While we found that there were various patterns (no change, increase, and decrease in substance use patterns), other studies have mostly found that substance use increased after a natural disaster. For instance, a study of substance use after Hurricane Maria found that, among people who inject drugs, increased from 3 to 23% after the storm (Abadie et al, 2022). After Hurricane Katrina, a study found that smoking cigarettes, drinking alcohol, and having alcohol consumption related problems were reported at a much higher rate than before the hurricane.…”
Section: Discussionmentioning
confidence: 99%
“…While the impact of COVID-19 on people with OUDs has been significant, people who inject drugs (PWID) and, in particular, Puerto Rican PWID bore a disproportionate percentage of overdose deaths [ 13 15 ]. Although epidemiological data is not yet available, it is likely that increased drug use frequency led not only to an increase in overdose episodes and deaths but also higher HIV and HCV (Hepatitis C virus) risks among this vulnerable population.…”
Section: Introductionmentioning
confidence: 99%
“…Potential mechanisms include changing drug use patterns and access to substances due to altered physical environment, and via poor mental health (e.g., depression, stress, anxiety) in the aftermath of a disaster [ 11 , 16 , 17 ]. Such events may disrupt communities and reduce access to drug treatment services which may further leave individuals vulnerable to poor substance use outcomes [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%